1973
DOI: 10.1113/jphysiol.1973.sp010345
|View full text |Cite
|
Sign up to set email alerts
|

The maturation of neuromuscular function in a multiply innervated structure: development of the longitudinal smooth muscle of the foetal mammalian gut and its cholinergic excitatory, adrenergic inhibitory, and non‐adrenergic inhibitory innervation

Abstract: SUMMARY1. The earliest components of the developing innervation of the rabbit intestine to be detected in this study were the cholinergic excitatory and the intrinsic inhibitory innervation. These developed simultaneously in the rabbit at 17 days of gestation. Both were also present in the mouse by the 16th day of gestation. Responsiveness of rabbit tissue to exogenous acetylcholine appeared together with the advent of a functional cholinergic innervation. Since excitatory responses were potentiated by eserine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 30 publications
(28 reference statements)
4
36
0
Order By: Relevance
“…These observations suggest that the intrinsic cholinergic nerve starts to function in the chick oesophagus as early as 10 days of incubation. The early appearance of functional cholinergic innervation to the smooth muscles of the chick oesophagus is consistent with the observation in the rabbit ileum (Gershon & Thompson, 1973), rat ileum (Miyazaki et al, 1982) and rat stomach (Ito et al, 1988). The C6-and atropine-sensitive response elicited by vagal nerve stimulation in the chick oesophagus appeared a day later than that induced by transmural nerve stimulation, suggesting that the oesophagus could accept the input from the vagus nerve at 11 days of incubation and that ganglionic transmission also develops immediately after neuro-effector transmission is established.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These observations suggest that the intrinsic cholinergic nerve starts to function in the chick oesophagus as early as 10 days of incubation. The early appearance of functional cholinergic innervation to the smooth muscles of the chick oesophagus is consistent with the observation in the rabbit ileum (Gershon & Thompson, 1973), rat ileum (Miyazaki et al, 1982) and rat stomach (Ito et al, 1988). The C6-and atropine-sensitive response elicited by vagal nerve stimulation in the chick oesophagus appeared a day later than that induced by transmural nerve stimulation, suggesting that the oesophagus could accept the input from the vagus nerve at 11 days of incubation and that ganglionic transmission also develops immediately after neuro-effector transmission is established.…”
Section: Discussionsupporting
confidence: 88%
“…which the response to nerve stimulation appears, both the nerve elements and the smooth muscle cells were observed to be morphologically immature (Gershon & Thompson, 1973). Morphological studies on the enteric nervous system indicated that the maturation of ganglion cells and synapses occurs slowly during the embryonic period (Bennett & Cobb, 1969;Daikoku et al, 1975;Gershon et al, 1981;Lolova, 1983a, b), sug-gesting that quantitative and qualitative changes in functional innervation may also take place during this period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with reports that the reactivity to transmitters precedes the functional innervation in rat vas deferens (Swedin, 1972) and chick heart (Pappano, 1977). However, in the rabbit intestine, the response to exogenous ACh appeared simultaneously with the onset of functional cholinergic innervation (Gershon & Thompson, 1973). There could be species differences.…”
Section: Responses To Noradrenalinementioning
confidence: 98%
“…It has been reported that stimulation of the intramural inhibitory neurones (non-adrenergic) in the gut caused the aftercontraction with (Holman & Hughes, 1965;Bennett, 1966) or without (Gershon & Thompson, 1973) preceding relaxation. Furthermore, it has also been observed that a non-cholinergic excitatory neurone causes an atropine-resistant contraction in avian and mammalian gastro-intestinal tracts (Ambache & Freeman, 1968;Nakazato, Sato & Ohga, 1970;Takewaki & Ohashi, 1977).…”
Section: Responses To Noradrenalinementioning
confidence: 99%